Implementation of public relations in building the image of educational institutions in madrasah aliyah - Nuzula, Jannatul Firdausi; Ariarta, Aliffany Pualam; Nur , Muhammad Amin; Fadilah, Inayatul (STAI Auliaurrasyidin Tembilahan, 2024)
A positive public image can enhance trust and interest in educational institutions. This study aims to examine: (1) the concept of public relations management, (2) the concept of institutional image, and (3) the implementation of public relations programs in building the institution's image. The research employs a qualitative method with a case study approach, involving the principal, vice principal of public relations, students, alumni, and the community. Data were collected through interviews and observations, then analyzed through data condensation, presentation, and conclusion drawing. The validity of the findings was verified through source and method triangulation. Results indicate that public relations management is conducted through several stages: (1) Planning is done at the beginning of the school year, aligning with the institution's vision, mission, and objectives; (2) Organizing involves collaboration across different departments; (3) Implementation adheres to principles of integration, sustainability, and honesty; and (4) Evaluation is routinely carried out by the internal public relations team. Furthermore, the public relations team works to build the institution's image by fostering trust and good relationships with local pesantren, providing optimal services to parents, and establishing institutional identity through flagship programs like